Larguras efetivas de lajes sem vigamento em prédios lateralmente carregados - Rodrigues, Paulo Fernando Neves (1989)
This work aims to present values for effective widths of laterally loaded flat plates floors using the finite element method. Works developed by other researchers are also presented. The results are compared and consequent conclusions are formulated.